Coal Exploration using Electrical Resistivity Method in Some Parts of Benue Trough, Nigeria - Olatunji , Saminu; Jimoh, Abdulgafar T. (Tanzania Journal of Science, 2020)
Geoelectrical resistivity sounding technique was used to delineate the occurrence and extents of coal seam. Fifteen points were sounded with Schlumberger configuration in the suspected coal deposit site bounded by longitudes 7.344° E and 7.366° E, and latitudes 7.318° N and 7.33° N. The vertical electrical sounding (VES) data were analyzed and the corresponding geo-electric parameters at various depths were modeled. The earth model within the study area was correlated with available lithology of a nearby mine site. The sounding signatures are KQHK and KHK curve types which revealed five to six distinct geo-electrical equivalent layers. The wet to dry sandy topsoil has resistivity range of 300–1000 Ωm and average thickness of 1.5 m. Next is a layer with higher resistivity range (1000–20000 Ωm). This layer, which extends to 14 m depth, is considered probably to be laterite, patched with sand in some places. Underlain this is a shale formation that laterally sandwiched the coal seam. The thickness and resistivity range of the coal seam is 1.5–3.4 m and 778–103000 Ωm, respectively, while the shale domain has resistivity range of 99–898 Ωm. Therefore, it could be concluded that the coal seam occurrence take shale as host rock in the area and the largest deposit appeared at the Eastern part of the area.